A Review of Medicinal Plants with Antiviral Activity Available in Bangladesh and Mechanistic Insight Into Their Bioactive Metabolites on SARS-CoV-2, HIV and HBV - Bachar, Sitesh C.; Mazumder, Kishor; Bachar, Ritesh; Aktar, Asma; Al Mahtab, Mamun (Frontiers in Pharmacology, 2021)
For the most part, plants have been accepted as a common source of medicine. Scientists have been inspired by the prevalence of infectious diseases to create new and more effective antiviral drugs. Medicinal plants have been established to be potent antiviral drug development sources with some advantages over conventional drug therapy due to their broad therapeutic potency and limited side effects. The development of safe, effective, and low-cost antiviral drugs is the top global drug development priority. Many viruses are not yet curable, and the mortality rates are high, such as the old viruses HIV, hepatitis, HPV, etc. This review provides an insight into Bangladeshi medicinal plants and their potential metabolites, enlightening their role in the development and application of alternatives in treating viral infections.